GIS and public health - Cromley, Ellen K.; McLafferty, Sara 1951- (New York The Guilford Press, 2012)
"Authoritative and comprehensive, this is the leading text and professional resource on using geographic information systems (GIS) to analyze and address public health problems. Basic GIS concepts and tools are explained, including ways to access and manage spatial databases. The book presents state-of-the-art methods for mapping and analyzing data on population, health events, risk factors, and health services, and for incorporating geographical knowledge into planning and policy. Numerous maps, diagrams, and real-world applications are featured. The companion Web page provides lab exercises with data that can be downloaded for individual or course use"--Provided by publisher.
Introduction -- 1. Geographic Information Systems -- 2. Spatial Data3. Spatial Databases for Public Health -- 4. Mapping Health Information -- 5. Analyzing Spatial Clustering of Health Events -- 6. Analyzing Environmental Hazards -- 7. Analyzing the Risk and Spread of Infectious Diseases -- 8. Exploring the Ecology of Vector-Borne Disease -- 9. Analyzing Access to Health Services -- 10. Locating Health Services11. Health Disparities -- 12. Public Participation GIS and Community Health.
Includes bibliographical reference and index.
Keywords: Geographic information systems; Public health -- Data processing